2017
DOI: 10.1140/epjp/i2017-11732-1
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation and interacting fields

Abstract: Hawking radiation is generally derived using a non-interacting field theory. Some time ago, Leahy and Unruh showed that, in two dimensions with a Schwarzschild geometry, a scalar field theory with a quartic interaction gets the coupling switched off near the horizon of the black hole. This would imply that interaction has no effect on Hawking radiation and free theory for particles can be used.Recently, a set of exact classical solutions for the quartic scalar field theory has been obtained.These solutions dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…First of all, it was shown that Hawking radiation persists [15,16] in free-field theories with modified dispersion relations for which the energy is always smaller than the Planck mass M p . 6 Renormalizable interactions were also studied [18][19][20] and no significant effect on Hawking radiation was found.…”
Section: Jhep01(2022)019mentioning
confidence: 99%
“…First of all, it was shown that Hawking radiation persists [15,16] in free-field theories with modified dispersion relations for which the energy is always smaller than the Planck mass M p . 6 Renormalizable interactions were also studied [18][19][20] and no significant effect on Hawking radiation was found.…”
Section: Jhep01(2022)019mentioning
confidence: 99%
“…From Equation , that expresses the group commutation rules, the motion equations for the nonzero field components Rfalseˆ=R01 (the longitudinal acoustic phonon field) and Sfalseˆ=R11 (the spatial strain field) decouple, yielding(t2cs2x2)Rfalseˆ+λcs2|Rfalseˆfalse|2Rfalseˆ=0(t2cs2x2)Sfalseˆ=0.Sfalseˆ(x,t) describes the fluctuations of the crystal strain field, that in higher dimensional domains are coupled to phonons, which may get scattered by them. Regarding the equation for the acoustic phonon Rfalseˆ(x,t), the parameter λ leads to a nonlinear oscillatory solution for Rfalseˆ with a dispersion relation given byωk2=λcs22ρR2+cs2k2where ρR is an integration constant depending on the cell characteristics. Equation can be derived by the Eulero–Lagrange equation from a Lagrangian that is a simplified form of Equation scriptLR=12(η…”
Section: Challenges In Gauging Spatial Symmetrymentioning
confidence: 84%
“…Sðx, tÞ describes the fluctuations of the crystal strain field, that in higher dimensional domains are coupled to phonons, which may get scattered by them. Regarding the equation for the acoustic phononRðx, tÞ, the parameter λ leads to a nonlinear oscillatory solution forR with a dispersion relation given by [57,58]…”
Section: Yang-mills Theory Of Acoustic Phonons In Crystalmentioning
confidence: 99%
“…First of all, it was shown that Hawking radiation persists [14] in free-field theories with modified dispersion relations for which the energy is always smaller than the Planck mass M p . 6 Renormalizable interactions were also studied [16][17][18] and no significant effect on Hawking radiation was found.…”
Section: Trans-planckian Problemmentioning
confidence: 99%